1963
DOI: 10.4315/0022-2747-26.4.114
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Medium for the Isolation and Enumeration of Enterococci in Dairy Products1

Abstract: Ten media, commonly used for the detection and isolation of streptococci of sanitary significance in water, dairy and other food products, were compared to establish a plating medium for the enumeration of enterococci in dairy products. To make all media suitable for comparison by the agar plate method, agar was added to those media which initially were recommended for use as broths. Criteria used in selecting the medium were high recovery, selectivity but not undue inhibition of enterococci and ease in obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1964
1964
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…1951) incubated at 30°C for 5 days anaerobically (GasPak); cycloheximide (Sigma Chemical, St Louis, MO, USA) was added (100 mg/L) to prevent the growth of yeasts in MRS agar and M17 agar (Kandler and Weiss 1986). Enterococci were grown on citrate azide agar (CAA; Saraswat et al . 1963) after 3 days at 37°C and Gram‐negative organisms on nutrient agar crystal violet (NACV) at 21°C for 24 h. All media were obtained from Merck, except AcA and CAA, which were made from the individual ingredients.…”
Section: Methodsmentioning
confidence: 99%
“…1951) incubated at 30°C for 5 days anaerobically (GasPak); cycloheximide (Sigma Chemical, St Louis, MO, USA) was added (100 mg/L) to prevent the growth of yeasts in MRS agar and M17 agar (Kandler and Weiss 1986). Enterococci were grown on citrate azide agar (CAA; Saraswat et al . 1963) after 3 days at 37°C and Gram‐negative organisms on nutrient agar crystal violet (NACV) at 21°C for 24 h. All media were obtained from Merck, except AcA and CAA, which were made from the individual ingredients.…”
Section: Methodsmentioning
confidence: 99%
“…Decimal dilutions were prepared in sterile peptone water (1.0 g/L) and plated in duplicate. Lactic acid bacteria (LAB) were grown anaerobically (Gas‐Pack system; BBL, Cockeysville, MD, USA) on MRS agar (pH 6.2) 4 at 30°C for 5 days; Gram + , catalase‐cocci on M17 agar at 30°C for 48 h, and enterococci on citrate azide agar (CAA) 5 at 37°C for 3 days. Cycloheximide (Sigma chemicals, St Louis, MO, USA) was added (100 mg/L) to MRS and M17 agar to prevent the growth of yeasts 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Saraswat et al 48 compared ten selective media and found citrate a i d e medium'59 to be the most effective for isolation of fecal streptococci from dairy products. The efficacy of citrate azide agar to meet the rigid requirements for enumeration of enterococci in milk products has also been reported by other researchers.…”
Section: Enumeration Isolation and Identificationmentioning
confidence: 98%